PENGARUH KUALITAS PENGETAHUAN PERPAJAKAN, MOTIVASI DAN EKONOMI TERHADAP MINAT MENGIKUTI BREVET PAJAK A & B (Studi Empiris Mahasiswa Akuntansi Universitas Islam Malang Dan Universitas Islam Negeri Maulana Malik Ibrahim) - Aulia Nurul Hidayah; Moh. Amin; Junaidi Junaidi (Universitas Islam Malang, 2022)
This study purpose to determine the effect of tax knowledge, motivation and economics on interest in participating in A & B tax brevet. This study is a quantitative study using primary data obtained from questionnaires and measured using the Likert Scale. The population in this study were Accounting Students Faculty of Economics and the Business, University of Islam Malang and State Islamic University of Maulana Malik Ibrahim. Sampling using the Slovin formula obtained the final result as many as 80 respondents. The method of determining the sample is purposive sampling. This data analysis technique uses SPSS 16.0 for windows. The results of the research show: 1) The variable of the quality of tax knowledge, motivation and influence simultaneously on the interest in participating in the A & B tax brevet, 2) According to the t test, the variable of the quality of taxation knowledge and partial effect on the interest in the A & B tax brevet, 3) According to t test Economic variables have no partial effect on interest in participating in A & B tax brevet.Keywords: Quality of Tax Knowledge, Motivation, Economy, Tax Brevet A & B